Identification and evaluation of the critical success factors for solar energy project in Malaysia using analytic hierarchy process (AHP) - Mokan, Kogila Vani (2021)
Energy sources is an essential part for all living things in the world. Malaysia is a gifted country with renewable energy sources which will never run out and constantly recharged by nature. Solar energy is one of the potential renewable energy sources in Malaysia that could generated sustainable power sources directly from sun. The problems that encourage conduct this research are import of fossil fuel that put a lot of burden on Malaysia’s economy, environmental issue, lack of awareness among public, lack of publication of critical success factors (CSFs) of solar energy project and methodology gap. In order to address these issues, this research aimed to identify the CSFs for solar energy project in local context, analysed the CSFs importance in solar energy project in Malaysia using analytic hierarchy process (AHP) method and evaluated the ranking of CSFs based on AHP result. Total 6 main CSFs namely economic, environment, technology, organization and management, government and social factor and 27 sub-factor were proposed in this research to develop AHP model. Besides, the data for this research were collected via online survey questionnaire from 73 solar energy companies in Klang Valley with 52% return rate of valid questionnaires. The collected data were analysed using Expert Choice software of AHP to rank the CSFs from most important factors. The finding revealed that environment factor (0.206) ranked as first priorities CSF followed by technology factor (0.195), economic factor (0.168), government factor (0.155), organization and management factor (0.142) and social factor (0.134) respectively. Moreover, reduce carbon dioxide emission (0.079), government policies (0.073), financial perspective (0.061), financial support (0.055) and reduce air pollution (0.048) were the priority ranking order of the top 5 sub-factor that identified in this research. Besides, the finding achieved in this research provide guideline for solar energy industry in Malaysia to manage and increase the quality of solar energy project successfully. Plus, the assessment of AHP model in this research served a better idea and knowledge for future researcher since the AHP model purpose in this research is new in local context.